2021
DOI: 10.1073/pnas.2109175118
|View full text |Cite
|
Sign up to set email alerts
|

Peptide nucleic acid–dependent artifact can lead to false-positive triplex gene editing signals

Abstract: Triplex gene editing relies on binding a stable peptide nucleic acid (PNA) sequence to a chromosomal target, which alters the helical structure of DNA to stimulate site-specific recombination with a single-strand DNA (ssDNA) donor template and elicits gene correction. Here, we assessed whether the codelivery of PNA and donor template encapsulated in Poly Lactic-co-Glycolic Acid (PLGA)-based nanoparticles can correct sickle cell disease and x-linked severe combined immunodeficiency. However, through this proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…PNA aggregates have been shown to interact nonspecifically with proteins and oligonucleotides, 44,45 which can impair their usefulness for in vivo applications such as gene editing. 46 The solubility of our secondary probes of different lengths, including HP18 (15-mer), HP17 (12-mer), HP16 (9-mer), and HP20 (8-mer), was assessed in a buffer used for lutetium-177 labeling (0.2 M NH 4 Ac; pH 5.5) at 25 °C (see Figure S19). Among these probes, the longest variant, HP18 (15mer), exhibited the lowest solubility, measuring at just 3 μM.…”
Section: Resultsmentioning
confidence: 99%
“…PNA aggregates have been shown to interact nonspecifically with proteins and oligonucleotides, 44,45 which can impair their usefulness for in vivo applications such as gene editing. 46 The solubility of our secondary probes of different lengths, including HP18 (15-mer), HP17 (12-mer), HP16 (9-mer), and HP20 (8-mer), was assessed in a buffer used for lutetium-177 labeling (0.2 M NH 4 Ac; pH 5.5) at 25 °C (see Figure S19). Among these probes, the longest variant, HP18 (15mer), exhibited the lowest solubility, measuring at just 3 μM.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the seemingly solid evidence of gene-editing by gPNA including in vivo 320 and in utero 321 studies in mouse models, a question has been raised whether the observed effects are real or just artifacts resulting from the possible aggregation of the (miniPEG) PNA onto the donor DNA. 322 The pyrrolidinyl acpcPNA has not yet been extensively studied for biological applications. In one report, the acpcPNA designed to target the NF-kB binding site in the promoter region of the Il6 gene was introduced to macrophage cells with the help of oxidized carbon nanoparticles and was shown to inhibit the stimulated production of Il6 mRNA as well as IL-6 protein levels in vitro.…”
Section: Modified Pna For Enhancement Of Cellular Uptake and Gene Reg...mentioning
confidence: 99%
“…However, despite the seemingly solid evidence of gene-editing by γPNA including in vivo 320 and in utero 321 studies in mouse models, a question has been raised whether the observed effects are real or just artifacts resulting from the possible aggregation of the (miniPEG) PNA onto the donor DNA. 322 …”
Section: Introductionmentioning
confidence: 99%
“…To enhance the formation of triplex structures, various strategies have been developed, including modifying the third oligo (e.g., base modification, [3,14] artificial base substitution, [15] sugar modification, [16,17] pseudopeptide backbone replacement [18,19] ) to improve its enthalpy contribution and promote binding to homopurine‐homopyrimidine duplexes. However, these chemical modifications are often costly and may lead to unpredictable thermodynamic consequences and potential biosafety concerns [20–23] . Another commonly used strategy involves the noncovalent intercalation of DNA binders to induce triplex formation by providing additional stacking forces [8,24] .…”
Section: Introductionmentioning
confidence: 99%